2010
DOI: 10.1007/s11104-010-0432-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil and root populations of fluorescent Pseudomonas spp. associated with seedlings and field-grown plants are affected by sorghum genotype

Abstract: Sorghum [Sorghum bicolor (L.) Moench] is valued for bioenergy, feed and food. Potential of sorghum genotypes to support differing populations of root-and soil-associated fluorescent Pseudomonas spp. or Fusarium spp., in two soils, was assessed. Culturable pseudomonads were enumerated from roots and soil of sorghum (Redlan and RTx433) and wheat (Lewjain) seedlings repeatedly grown in cycled soils in the growth chamber. Pseudomonads and Fusarium spp. were assessed from roots and soil of field-grown sorghum along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
0
12
1
Order By: Relevance
“…We investigated the structure of streptomycete communities in soils associated with different plant host species and across a gradient of plant community richness. Previous work has indicated that soil microbial communities are differentially impacted by host plant species (Mazzola et al ., ; Funnell‐Harris et al ., ) and by communities of varying diversity (Chung et al ., ; Lamb et al ., ). However, our data provide evidence for interaction between these two factors, with plant community characteristics altering the influence of individual host species on soil microbes.…”
Section: Discussionmentioning
confidence: 97%
“…We investigated the structure of streptomycete communities in soils associated with different plant host species and across a gradient of plant community richness. Previous work has indicated that soil microbial communities are differentially impacted by host plant species (Mazzola et al ., ; Funnell‐Harris et al ., ) and by communities of varying diversity (Chung et al ., ; Lamb et al ., ). However, our data provide evidence for interaction between these two factors, with plant community characteristics altering the influence of individual host species on soil microbes.…”
Section: Discussionmentioning
confidence: 97%
“…Cycling of sorghum and wheat seedlings was conducted as previously described (Funnell-Harris et al 2010). Sorghum grain of cultivars Redlan and RTx433 were produced in greenhouses at University of Nebraska, Lincoln (UNL).…”
Section: Growth Chamber Sorghum and Wheat Seedling Cyclingmentioning
confidence: 99%
“…Soil used was collected from post-harvest sorghum plots at UNL research fields at Lincoln (2008) and Ithaca (2007), NE, as previously described (Funnell-Harris et al 2010). Soil at Lincoln was a Kennebec silt loam, a fine-silty, mixed, superactive, mesic Cumulic Hapladolls.…”
Section: Growth Chamber Sorghum and Wheat Seedling Cyclingmentioning
confidence: 99%
See 2 more Smart Citations